Effects of Rumensin or Rumensin-Tylan combination on steer performance and liver abscess control - Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
Combining Tylan with Rumensin dramatically reduced abscessed liver incidence, compared with that of steers fed a non-medicated control ration or Rumensin without Tylan. Only one steer out of 50 on the Rumensin plus Tylan combination had an abscessed liver, whereas livers from 16 of the control steers and 27 on Rumensin were condemned. There were no significant differences in daily gain among treatments; however, Rumensin plus Tylan improved feed efficiency by 9.4% compared with that of the control. Rumensin alone improved efficiency by 6%.
Keywords: Beef; Rumensin; Rumensin-Tylan; Steer; Performance; Liver abscess